2010
DOI: 10.1186/1471-2407-10-614
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of sonic hedgehog-GLI1 downstream target genes PTCH1, Cyclin D2, Plakoglobin, PAX6 and NKX2.2 and their epigenetic status in medulloblastoma and astrocytoma

Abstract: BackgroundThe Sonic hedgehog (Shh) signaling pathway is critical for cell growth and differentiation. Impairment of this pathway can result in both birth defects and cancer. Despite its importance in cancer development, the Shh pathway has not been thoroughly investigated in tumorigenesis of brain tumors. In this study, we sought to understand the regulatory roles of GLI1, the immediate downstream activator of the Shh signaling pathway on its downstream target genes PTCH1, Cyclin D2, Plakoglobin, NKX2.2 and PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
62
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 46 publications
6
62
0
Order By: Relevance
“…However, we found that Nkx2-2as plays a tumor-suppressive role independent of Nkx2-2, consistent with the previous finding that in cis regulation of Nkx2-2 is dispensable for the prodifferentiation role of Nkx2-2as in neural stem cells (25). Furthermore, Shahi and colleagues found that Nkx2-2 is directly targeted and upregulated by Gli1 in MB cells (37), which in combination with our current findings suggests that this genomic region is involved in the pathogenesis of Shh-type MBs. While both transcription factors are critically involved in Shh signaling, previous studies suggested that Gli2 but not Gli1 is required for Shh signaling and mediates inappropriate activation of the pathway (38), which is in agreement with our finding that Nkx2-2as is downregulated solely by Gli2 via transcriptional activation of FoxD1.…”
Section: Discussionsupporting
confidence: 81%
“…However, we found that Nkx2-2as plays a tumor-suppressive role independent of Nkx2-2, consistent with the previous finding that in cis regulation of Nkx2-2 is dispensable for the prodifferentiation role of Nkx2-2as in neural stem cells (25). Furthermore, Shahi and colleagues found that Nkx2-2 is directly targeted and upregulated by Gli1 in MB cells (37), which in combination with our current findings suggests that this genomic region is involved in the pathogenesis of Shh-type MBs. While both transcription factors are critically involved in Shh signaling, previous studies suggested that Gli2 but not Gli1 is required for Shh signaling and mediates inappropriate activation of the pathway (38), which is in agreement with our finding that Nkx2-2as is downregulated solely by Gli2 via transcriptional activation of FoxD1.…”
Section: Discussionsupporting
confidence: 81%
“…In general, Nkx2.2 expression was high in the low grade tumors (class II and III -anaplastic astrocytoma) compared to high grade glioblastoma multiforme (class IV-GBM) (Riemenschneider et al, 2004). Nkx2.2 is also expressed in medulloblastoma cell lines and primary tumor samples and Nkx2.2 expression is dependent on Shh-Gli1 pathway (Shahi et al, 2010). Upon knockdown of Gli1 in medulloblastoma cell line with short interfering RNAs (siRNA), Nkx2.2 expression was reduced compared to control negative siRNA treated cells (Shahi et al, 2010), suggesting that Gli1 positively regulates Nkx2.2 expression.…”
Section: Role Of Nkx22 In Brain Cancermentioning
confidence: 94%
“…Interestingly, both Pax6 and Nkx2.2 are targets of the major Shh downstream transcription factor Gli1 in medulloblastoma cell lines and tissues (Shahi et al, 2010). Moreover, both genes have been implicated in stem cell maintenance (Hu et al, 2009;Zhang et al, 2010); therefore, it would be fruitful to understand these genes in the context of Shh signaling in TSC-mediated medulloblastoma biogenesis.…”
Section: Transcription Factors Implicated In Sonic Hedgehog Signal Trmentioning
confidence: 99%
“…Bcl-2 and cyclin D1 are considered important target genes of the Shh signaling pathway, directly affecting cell proliferation and survival (33). Research indicates that high levels of cyclin D1 are associated with activation of the transcription factor Gli (34). Furthermore, the pro-survival protein Bcl-2 is upregulated in various tumors, including human breast cancers (35).…”
Section: A B Cmentioning
confidence: 99%